The Effectiveness of Buffer Solution Module Based on Guided Discovery Learning Model for Student’s Learning Outcomes - Isti, Meila; Yerimadesi, Yerimadesi (Entalpi Pendidikan Kimia, 2024)
This study aims to determine the effectiveness of the buffer solution module based on the guided discovery learning model on student learning outcomes at SMAN 1 Nan Sabaris. The type of research is experimental research with one group pretest posttest design. The population in this study were students in class XI IPA at SMAN 1 Nan Sabaris in the 2022/2023 academic year. The sampling technique used is simple random sampling. In this study, students in class XI IPA 2 were selected as the sample class. The instrument used was a multiple choice test consisting of 20 questions with 5 answer choices. The test is carried out by administering an initial test (pretest) and a final test (posttest). The data obtained will be analyzed by N-Gain Test, Normality Test, and Hypothesis Test. Based on the research results, an N-Gain value of 0.62 is obtained in the medium category. The significance value in the hypothesis test obtained is smaller than the significant level of 0.05 (significant value 0.000 <0.05). Thus, it can be concluded that the use of a buffer solution module based on the guided discovery learning model is effective in improving student learning outcomes.